Advances in Protective Personnel and Vehicle Armors - Z. (Gama) Haque, Bazle; M. Kearney, Meaghan; W. Gillespie, John (Recent Patents on Materials Science, 2012)
From the beginning of mankind, people have fought over territories, religion, food, and honor. However, as mankind became more civilized, weaponry became more advanced. There is a continuous need to develop armor to better protect soldiers from the ever changing weaponry. In order to discuss recent patents in body armor and vehicular armor, the history and development of weapons and armor will be discussed. After the history and development of weapons and protective armor, recent patents in body armor and vehicular armor will be reviewed. Body armor patents are broken down into fabrics, armor systems, and helmets. Vehicular armor is divided into ceramics, attachable armor, composites, and transparent armor. The patents reviewed are a sample of the ideas and designs being created in the industry in order to better protect soldiers, policemen, and the like from harm. Analyzing the different aspects of body armor and vehicular armor we gain a better sense of the specific needs, in terms of protection, that have yet to be developed.
Keywords: patents